Saturated liquid kinematic viscosity, surface tension and thermal diffusivity of two low-GWP refrigerants 3, 3, 3-trifluoropropene (R1243zf) and trans-1-chloro-3, 3, 3-trifluoro-1-propene (R1233zd(E)) by light scattering method. (July 2021) - Zhao, Guanjia; Yuan, Zemin; Zhang, Xing; Yin, Jianguo; Ma, Suxia
Highlights: The two refrigerants of R1243zf and R1233zd (E) could be used as the low-GWP working fluid. Thermophysical properties of the selected R1243zf and R1233zd (E) were investigated. Light scattering method was used for the determination of thermophysical properties. Correlations were proposed for the investigated thermophysical properties. Abstract: To facilitate the application of low-GWP refrigerants in the refrigeration and heat pump systems, it is highly necessary to obtain their thermophysical properties including the liquid surface tension, viscosity and thermal diffusivity. In the present study, these thermophysical properties of two low-GWP refrigerants 3, 3, 3-trifluoropropene (R1243zf) and trans-1-chloro-3, 3, 3-trifluoro-1-propene (R1233zd(E)) were investigated by using the light scattering method under saturation conditions. With the experimental data, a van der Waals type equation for surface tension and polynomial equation with an additional term to capture the trend close to the critical point for viscosity and thermal diffusivity were proposed for the future applications.